The Effectiveness of Adding Different Sucrose in Tris-Egg Yolk Diluent on the Sperm Fertility of Sexing Swamp Buffalo (Bubalus bubalis): Adding Different Sucrose in Tris-Egg Yolk Diluent on the Sperm Fertility of Sexing Swamp Buffalo - Yendraliza Yendraliza; Allif Bukhori; Edi Erwan; Ria Sari Gail Sianturi; Diana Andrianita Kusumaningrum; Muhamad Rodiallah; Zumarni (Journal of Tropical Life Science, 2023)
Spermatozoa sexing requires a diluent that can protect and provide an optimal environment to maintain the quality of spermatozoa. This study targets to determine the effectiveness of adding sucrose to tris-egg yolk diluent on the sperm quality of the swamp buffaloes produced by sexing with the egg albumin method. Semen was collected once a week for 12 consecutive weeks with an artificial vagina from three male buffaloes at the Indonesian Center for Animal Research and Development (ICARD) in April - June 2021. Semen was separated by sedimentation using 10% and 30% egg albumins. Semen from sexing was divided into four diluent treatments, namely 20% tris-egg yolk (TEY), TEY+0% sucrose, TEY+0.2% sucrose, TEY+0.3% sucrose, and TEY+0.4% sucrose. Parameters measured included: motility, viability, intact plasm membrane, and intact acrosome cap of buffalo sperm. The results showed the motility of X sperm: 43.75-47.5%, Y sperm: 40-45%, the viability of X sperm: 78.25-79.75% and Y sperm: 77.25-79.75%, intact plasm membrane of X sperm: 70.5-71.5% and Y sperm: 70.5-71%, and viable acrosome-intact for X sperm: 79-80% and Y sperm: 78.75-79.5%. The addition of sucrose up to 0.4% into tris-egg yolk diluent was proven can maintain motility, viability, and integrity of cell membrane and acrosome of spermatozoa of water buffalo that was sexed with egg albumin.